Trace Elements in Sediments of Selected Gutters and Bar – Beach, Lagos, Nigeria - CL Overah; CMA Iwegbue; EK Ossai; GE Nwajei (Journal of Applied Sciences and Environmental Management)
Sediment samples were collected from selected gutters and Lagos bar beach for the investigation of trace element concentrations. The metals investigated were chromium, lead, arsenic, selenium, cadmium and barium using the atomic absorption spectrophotometry. The results obtained further revealed elevated concentrations metals from both selected gutters and the Lagos bar beach. It was also observed that the Lagos bar beach is the receiving end of all the pollution loads arising from the channeled gutters. These elevated trace element concentrations obtained in sediment in this study were compared with other similar studies. The sediment contaminations by metals were traceable to industries and anthropogenic substances in Lagos metropolis.